Analysis of Total Suspended Solid (TSS), nitrite, nitrate and runoff changes during rainfall events at River Kurambik, Lake Maninjau. Issue 1 (June 2021) - Subehi, L; Ridwansyah, I; Apip,; Yulianti, M; Dianto, A; Wisesa, E T
Abstract: Lake Maninjau is a caldera lake with a volcano-tectonic type. The existing land management of Lake Maninjau catchment area influenced water quality, included River Kurambik as one of the rivers that flow into Lake Maninjau. It influenced degradation of water quality, nutrient enrichment and exceeded the carrying capacity. The source of pollutants, especially non-point sources pollution can be a point source in large numbers. For example, runoff from agricultural areas containing pesticides and fertilizers, runoff from residential areas (domestic). In order to gain insight into the effect of watershed conditions on water quality in Lake Maninjau, we statistically analyzed Total Suspended Solid (TSS), Nitrite, Nitrate, discharge, water temperature (Tw) and, air temperature (Ta) at River Kurambik, Lake Maninjau. Besides water level and water temperature (HOBO sensor), also Teledyne ISCO sampler equipment was used to take sample water for analysis. Some results showed the relation among parameters such as TSS, Nitrite, Nitrate, discharge, and water temperature as long as our observation in periods September – November 2018. Based on data, it could be explained that the seasonal variability of atmospheric conditions influenced fluctuations in air and water temperature nearly proportionally (R 2 = 0, 883). The change of discharge influenced Total Suspended Solid (TSS) significantly (R2 = 0, 917). It indicated the land use change contributed to the water quality during rainfall events through runoff sediment and materials into the lake. On the other hand, Nitrite, Nitrate parameters seemed to have various changes during rainfall events. The land use management and economic values of these lakes and ecosystem should be elucidated. In order to maintain the sustainability of the lake, land cover management at the catchment area is also necessary for the next study.